DETERMINANTS OF SPATIAL MARKET INTEGRATION OF GARLIC IN INDONESIA - Sandra, Indah Kartika; Siregar, Indah Adelina; Varwasih, Mia Wananda (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
Indonesia's dependence on the international market causes garlic prices to tend to fluctuate. Fluctuations in garlic prices tend to follow the amount of production and available import supply. Because Indonesia is an archipelagic country, garlic prices vary in each province. The availability and demand for garlic in each province are different, as well as fluctuations and disparities in garlic prices between regions, which are driving factors for interregional trade, which indicates the integration of the garlic market in Indonesia. The purpose of this study was to analyze the determinants of spatial garlic market integration in Indonesia. The types of data used are cross-section data on the amount of garlic consumption by province, gross regional domestic product by province, distance between reference and follower provinces, amount of garlic production by province, number of markets by province, length of paved roads by province in 2020 sourced from the Central Statistics Agency and Google Map. The analysis method used is multiple linear regression. The results of the study indicate that the determinants of spatial garlic market integration at the consumer level in Indonesia are the amount of consumption of follower provinces, gross regional domestic product of reference and follower provinces, and the distance between reference and follower provinces. Based on the results of the analysis, the suggestion from this study is that to improve the efficiency of garlic marketing in Indonesia, especially related to market integration, the government needs to pay attention to the determining factors of market integration.